2012
DOI: 10.1021/ic202156y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of RuO2Crystallization in Borosilicate Glass: An Originalin SituESEM Approach

Abstract: Ruthenium, a fission product arising from the reprocessing of spent uranium oxide (UOX) fuel, crystallizes in the form of acicular RuO(2) particles in high-level waste containment glass matrices. These particles are responsible for significant modifications in the physicochemical behavior of the glass in the liquid state, and their formation mechanisms are a subject of investigation. The chemical reactions responsible for the crystallization of RuO(2) particles with acicular or polyhedral shape in simplified r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 47 publications
(76 reference statements)
0
22
0
Order By: Relevance
“…[10][11][12][13] This is the case of Ga oxide NCs in silicate glass, which is one of the prototypal systems of oxide-in-oxide nanostructured glasses together with SnO 2 -doped silica. 14 Stability and thermal evolution of Ga-oxide nanophases are expected to be largely different from the freestanding and pure compound.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] This is the case of Ga oxide NCs in silicate glass, which is one of the prototypal systems of oxide-in-oxide nanostructured glasses together with SnO 2 -doped silica. 14 Stability and thermal evolution of Ga-oxide nanophases are expected to be largely different from the freestanding and pure compound.…”
Section: Introductionmentioning
confidence: 99%
“…Third, for crystallization/sintering processes occurred at either high or low temperature (relative to room temperature, ≈25 °C), the corresponding morphological evolution and growth mechanism can, of course, be monitored under ESEM by using different temperature‐controlling stages. For example, the evolution of morphology and size distribution of reaction products during crystallization or sintering of glass/ceramic materials can be imaged by ESEM at high temperature . Boucetta et al observed the changes in morphology and composition of the ruthenium compounds formed during an in situ heat treatment in ESEM operated at 30 kV.…”
Section: Recent Applicationsmentioning
confidence: 99%
“…4. HT-ESEM image sequence illustrating the formation and dissolution of Na2SiO3 intermediary phase (Boucetta et al (2012)) The reaction between NaNO 3 and a simplified sodo-boro-silicate glass yields to the spreading of liquid NaNO 3 at the glass surface and to the formation of intermediary Na 2 SiO 3 and "Na 2 O-B 2 O 3 " phases above 306°C (see Boucetta et al (2012) for more details). The image sequence that illustrates the evolution of the intermediary phases (494-659°C) followed by their local melting in contact with the silicate melt (727-894°C) are reported in figure 4.…”
Section: Applications In the Field Of Nuclear Glass Elaborationmentioning
confidence: 99%
“…This combination allows studying directly sample morphology modifications occurring during sample heat-treatment. It has been successfully used to study several phenomena such as the corrosion of metals (Jonsson et al, 2011), oxidation of metals (Oquab & Monceau (2001); Schmid et al (2002); Reichmann et al (2008); Mège-Revil et al (2009) ;Quémarda et al (2009); Delehouzé et al (2011)), reactivity at high temperature (Maroni et al (1999); Boucetta et al (2012)), phase changes (Fischer et al (2004); Hung et al (2007); , hydrogen desorption (Beattie et al ( , 2011, redox reactions (Klemensø et al (2006), microstructural modifications (Bestmann et al (2005);Fielden (2005); Yang (2010)), magnetic properties (Reichmann et al (2011)), sintering (Sample et al (1996); Srinivasan (2002); Marzagui & Cutard (2004); Subramaniam (2006); Courtois et al (2011);Joly-Pottuz et al (2011);Goel et al (2012); Podor et al (2012)), thermal decomposition (Gualtieri et al (2008); Claparède et al (2011);Hingant et al (2011);Goodrich & Lattimer (2012)), crystallisation (Gomez et al (2009)) in melts (Imaizumi et al (2003); Hillers et al (2007); Vigouroux et al (2013)) and the self-repairing -self-healing -properties of materials (Wilson & Case (1997); Coillot et al (2010Coillot et al ( , 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation